Design of novel aqueous micellar two-phase systems using ionic liquids as co-surfactants for the selective extraction of (bio)molecules - Vicente, Filipa A. (2014)
Aqueous micellar two-phase systems (AMTPS) using surfactants have been widely applied as an advantageous extraction technology for a wide range of (bio)molecules. When composed by two surfactants (the second one used as the co-surfactant), the extractive performance of such systems is considerably boosted. In this context, this work looks at ionic liquids (ILs) as a new class of tunable co-surfactants to be applied in AMTPS. Three distinct families of ILs, namely imidazolium, phosphonium and quaternary ammonium were applied in the design of the binodal curves of novel AMTPS based on the nonionic surfactant Triton X-114. On these systems it was investigated the impact of the IL absence/presence, concentration and structural features on the binodal curves behavior. Aiming at evaluating their applicability as extraction systems, partitioning studies of two targeted (bio)molecules, namely the protein Cytochrome c (Cyt c) and the dye/model drug Rhodamine 6G (R6G), were carried out. It is shown that the presence of ILs as co-surfactants is able not only to enhance the partition coefficients of Cyt c (indicated as logKCyt c) from 0.59 ± 0.12 up to 1.51 ± 0.14, but also to improve the selectivity parameter (SR6G/Cyt c) from 925.25 up to 3418.89. The results here obtained open new perspectives in the design of liquid–liquid separation processes, transversal to various fields and a wide range of applications